2016
DOI: 10.3390/ijms17111789
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Juice Consumption Modifies the Urinary Peptide Profile in Sprague-Dawley Rats with Induced Hepatic Steatosis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disorder in Western countries, with a high prevalence, and has been shown to increase the risk of type 2 diabetes, cardiovascular disease (CVD), etc. Tomato products contain several natural antioxidants, including lycopene—which has displayed a preventive effect on the development of steatosis and CVD. Accordingly, the aim of the present work was to evaluate the effect of tomato juice consumption on the urinary peptide profile in rats with NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Zeng et al [69] have demonstrated that lycopene improved insulin sensitivity in mice that were fed a high fat diet. Lycopene is known to raise insulin levels and concomitantly decrease body glucose levels [70,71]. Tomatoes have been considered beneficial in hyperglycemic/diabetic conditions because they mitigate diabetes induced tissue damage, atherosclerosis, inflammation, oxidative stress etc.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al [69] have demonstrated that lycopene improved insulin sensitivity in mice that were fed a high fat diet. Lycopene is known to raise insulin levels and concomitantly decrease body glucose levels [70,71]. Tomatoes have been considered beneficial in hyperglycemic/diabetic conditions because they mitigate diabetes induced tissue damage, atherosclerosis, inflammation, oxidative stress etc.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples for the application of multi‐dimensional marker were published , and the application of CE‐MS in urinary peptidomics for the diagnosis of CKD was reviewed recently . Urinary peptidomics by CE‐MS was furthermore used for the identification of biomarkers for chronic obstructive pulmonary disease , diastolic left ventricular dysfunction , end‐stage renal disease , chronic graft‐versus‐host disease , non‐alcoholic fatty liver disease and systemic lupus erythematosus . A chiral CE‐MS method was published by Švidrnoch to determine D/L‐2‐hydroxyglutaric acid without derivatization in urine as biomarker for a rare neurometabolic disorder .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…CE-MS of peptides has become quite a routine technique and is applied frequently in untargeted proteomics and peptidomics fields. For example, urine samples were screened for peptides as suitable biomarkers of disease, revealing specific biomarkers related to heart failure, deep vein thrombosis, and pulmonary embolism . Related to this, the suitability of mice as models for human aging was investigated by investigating the urinary proteome of the mice .…”
Section: Applicationsmentioning
confidence: 99%